Globalisation, participatory democracy and inclusive governance: Experiences in India - Sangita, S.N.; Jyothi, T.K. (2009)
This article examines the role of participatory democracy in promoting inclusive governance (responsive, efficient and equitable) in the context of globalisation. The authors argue that the democratic decentralisation can empower the disadvantaged particularly from rural areas to protect their interests from the negative implication of globalisation. Secondly, democratic decentralisation can also facilitate the delivery of various services efficiently and equitably meant for the disadvantaged in the context of globalisation. - Reproduced.
Keywords: Decentralization - India; Public administration - India; Globalization - India; Democratization - India; Democratization